Knee and ankle joint stiffness in sprint running - Kuitunen, S.; Komi, P. V.; Kyröläinen, H. (Medicine & Science in Sports & Exercise, 2002)
INTRODUCTION: Stiffness has often been considered as a regulated property of the neuromuscular system. The purpose of this study was to examine the ankle and knee joint stiffness regulation during sprint running. METHODS: Ten male sprinters ran at the constant relative speeds of 70, 80, 90, and 100% over a force platform, and ground reaction forces, kinematic, and EMG parameters were collected. RESULTS: The results indicated that with increasing running speed the average joint stiffness (change in joint moment divided by change in joint angle) was constant (7 N.m.deg-1) in the ankle joint and increased from 17 to 24 N.m.deg-1 (P < 0.01) in the knee joint. CONCLUSION: The observed constant ankle joint stiffness may depend on (constant) tendon stiffness because of its dominating role in triceps surae muscle-tendon unit. Thus, we conclude that in sprint running the spring-like behavior of the leg might be adjusted by changing the stiffness of the knee joint. However, in complicated motor task, such as sprint running, ankle and knee joint stiffness might be controlled by the individual mechanical and neural properties.